Sistem Informasi Pembayaran Sumbangan Pembinaan Pendidikan (Spp) Berbasis Web Pada Markaz Quran Utrujah - Fahri Hamadani; Eko Wijaya (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Payment tuition is a school financial component that handles administrative tasks to manage incoming and outgoing cash flows in an educational institution. Utrujah International Islamic College has a payment tuition process that is still experiencing problems because it is still processing financial data manually, namely by recording transactions in a book and using Microsoft Excel for reporting, so the process of paying fees there is still problematic. Therefore it is prone to errors in the procedure for recording transactions. This design aims to improve school administration payment services, speed up data management and prevent data input errors. Making a web-based system will be made using the waterfall and UML methods which will be discussed in this study. This payment tuition system was successfully built with waterfall method and using the PHP programming language. System testing was successfully carried out using blackbox testing.